Insights From Early Clinical Trials Assessing Response to mRNA SARS-CoV-2 Vaccination in Immunocompromised Patients - Baron, Frédéric; Canti, Lorenzo; Ariën, Kevin K.; Kemlin, Delphine; Desombere, Isabelle; Gerbaux, Margaux; Pannus, Pieter; Beguin, Yves; Marchant, Arnaud; Humblet-Baron, Stéphanie (Frontiers in Immunology, 2022)
It is critical to protect immunocompromised patients against COVID-19 with effective SARS-CoV-2 vaccination as they have an increased risk of developing severe disease. This is challenging, however, since effective mRNA vaccination requires the successful cooperation of several components of the innate and adaptive immune systems, both of which can be severely affected/deficient in immunocompromised people. In this article, we first review current knowledge on the immunobiology of SARS-COV-2 mRNA vaccination in animal models and in healthy humans. Next, we summarize data from early trials of SARS-COV-2 mRNA vaccination in patients with secondary or primary immunodeficiency. These early clinical trials identified common predictors of lower response to the vaccine such as anti-CD19, anti-CD20 or anti-CD38 therapies, low (naive) CD4+ T-cell counts, genetic or therapeutic Bruton tyrosine kinase deficiency, treatment with antimetabolites, CTLA4 agonists or JAK inhibitors, and vaccination with BNT162b2 versus mRNA1273 vaccine. Finally, we review the first data on third dose mRNA vaccine administration in immunocompromised patients and discuss recent strategies of temporarily holding/pausing immunosuppressive medication during vaccination.